Positron Emission Computed Tomography Imaging of Synaptic Vesicle Glycoprotein 2A in Alzheimer’s Disease - Kong, Yanyan; Zhang, Shibo; Huang, Lin; Zhang, Chencheng; Xie, Fang; Zhang, Zhengwei; Huang, Qi; Jiang, Donglang; Li, Junpeng; Zhou, Weiyan; Hua, Tao; Sun, Bomin; et al. (Frontiers in Aging Neuroscience, 2021)
Alzheimer's disease (AD), the most common form of dementia, has not yet developed a particularly effective drug. Early diagnosis of AD is of great significance to control the development of the disease. Synaptic loss is an important pathology in the early stage of AD, therefore the measurement of synaptic density using molecular imaging technology may be an effective way to diagnose early AD. synaptic vesicle glycoprotein 2A (SV2A) is a specific target molecule for epileptic drugs. PET imaging agents based on SV2A can quantify synaptic density. In view of the fact that synaptic loss is the pathology of both epilepsy and AD, this review summarizes the potential role of SV2A in the pathogenesis of AD, and suggests that SV2A should be used as an important target molecule of PET imaging agent for the early diagnosis of AD.